Screening of pesticide residues in Traditional Chinese Medicines using modified QuEChERS sample preparation procedure and LC-MS/MS analysis - Li, Rui-Xing; Li, Min-Min; Wang, Tao; Wang, Tie-Lin; Chen, Jie-Yin; Francis, Frédéric; Fan, Bei; Kong, Zhi-Qiang; Dai, Xiao-Feng (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2020)
•108 pesticides in Traditional Chinese Medicines were determined simultaneously.•Traditional Chinese Medicines are difficult matrices for residue analysis.•C18 and anhydrous MgSO4 were used as the dSPE sorbent.•92% of real samples were detected with pesticide residues.•Paclobutrazol showed a high residue level in O. japonicas. A robust and high-throughput method was developed for the determination of 108 pesticide residues in Traditional Chinese Medicines (TCMs) simultaneously using a combination of UHPLC-MS/MS analysis and the modified QuEChERS method. Extraction was carried out in acetonitrile containing 0.75% (v/v) acetic acid with ultrasonication for 15 min; MgSO4 and C18 were used as the dispersive-solid phase extraction sorbents. The method exhibited good linearity (r2 > 0.9901), in addition to good selectivity, precision and repeatability. More than 92% of pesticides exhibited high rates or recovery in the 70–120% range. This method showed high sensitivity, with Limits of Quantitation in the 0.01–20 ng/mL range in Cortex Moutan, and 0.01–50 ng/mL in the other TCMs. The method was employed for the analysis of 39 real samples from different habitats, and pesticides were detected in 92.3% of the samples, with 26 pesticides being detected in these three TCMs. More than four pesticides were detected in a third of the samples. Among them, tebuconazole was detected in all the three TCMs with 0.22–22.02 μg/kg concentration, which was lower than the provisions in GB 2763-2019 (50 μg/kg). In addition, the paclobutrazol detection rate in Ophiopogon japonicus was 100%, and the detected concentrations of 9 samples exceeded the Maximum Residue Levels defined for vegetables (50 μg/kg). Considering there are no regulations that govern the limits of pesticide residues in the three TCMs in China, we recommend the acceleration of efforts to introduce appropriate regulations.